An investigation on Unprotected Loss of Flow Accident in Th–Pu metal fuelled 500 MWe fast reactor. (February 2015) - Stephen, Neethu Hanna; Sathiyasheela, T.; Paul, Debanwita; Devan, K.; Keshavamurthy, R.S.; Reddy, C.P.
Highlights: Th- Pu metal FBR core reactivity coefficients are estimated. Static and transient behavior of Th–Pu core are compared with U–Pu–6Zr core. Under ULOFA, Th–Pu reactor reaches safe shutdown with passive SGDHRS. Abstract: This study focuses on computing static reactivity coefficients and analyzing Unprotected Loss of Flow Accident in a Th–Pu fuelled metal reactor. An attempt is also done to compare the static and dynamic performance of the fresh core with characteristics of U–Pu–6Zr fuelled 500 MWe metal reactor. Isothermal temperature coefficient and power coefficients are evaluated in the steady state and found to be negative. The excess reactivity and control rod worth requirements of Th–Pu metal core are assumed similar to that of U–Pu–6Zr metal core. In the Unprotected Loss of Flow Accident (ULOFA) analysis, with flow coast down initiated by station black out, it is found that power to flow ratio is increasing initially up to 53 s and then starts to reduce continuously. Power to flow ratio is found to be less than 2 at all times thus ensuring the absence of coolant boiling in the entire core. Sodium voiding starts around 886 s in the upper axial blanket and provide negative reactivity. Also it will not propagate to the core center ensuring the probability for core disruptive accident a remote one. Net reactivity feedback is negative and the major contribution is from core radial expansion. Within 12 min, the power drops to 32 MWt, making it possible for Safety Grade Decay Heat Removal (SGDHR) system to start heat removal from core ensuring safe shutdown of reactor. Sensitivity analysis by considering an uncertainty margin of ±10% in thermo physical properties of fuel composition shows that feedback reactivity of the Th–Pu system is insensitive and the conclusion on the safe shutdown remains unaltered. From this study it is found that inherent safety of Th–Pu metal fuel core is better than that of reactor core fuelled with U–Pu–6Zr metal type under ULOFA condition.